Muscular Dystrophy A Concise Guide - Huml, Raymond A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This practical and concise guide offers an overview of muscular dystrophy's (MD) complicated features, treatment options and general resources.  New treatments and a greater understanding of proteins and structures associated with MD are discussed along with long-term patient care.  Also included are clinical and developmental challenges within the current regulatory landscape and recent scientific and clinical advances.  Muscular Dystrophy: A Concise Guide offers clinicians, researchers, pharmaceutical executives and patient advocacy groups an easy-to-read reference that provides the necessary perspectives of the care giver and patient.
1. Introduction to Muscular Dystrophy -- 2.Muscular Dystrophy: Historical Background and Types -- 3.FSHD: The Most Common Type of MD? -- 4.Duchenne and Becker Muscular Dystrophies: Underlying Genetic and Molecular Mechanisms -- 5.An Overview of the Muscular Dystrophies: Underlying Genetic and Molecular Mechanisms -- 6.Transition from Childhood to Adult in Patients with Muscular Dystrophy -- 7.Overview of Current Treatments for Muscular Dystrophy -- 8.Physical Therapy and Orthotic Devices for Patients with Muscular Dystrophy -- 9.Orthopedic Care of Children with Muscular Dystrophy -- 10.Global Regulatory Landscape -- 11.Key Challenges to the Approval of Products to Treat Patients with Muscular Dystrophy -- 12.Pharmaceutical Products and Non-Pharmaceutical Interventions as Potential Treatments for Patients with Muscular Dystrophy -- 13.US Patient Advocacy Groups -- 14.Global and National Patient Registries -- 15.Summary -- Index.
Keywords: Neurology .; Pharmacotherapy; Medicine; Neurology; Pharmacotherapy; Medicine/Public Health, general